Relationship between Psychological Profile and Academic Achievement of Medical and Dental Students at Isfahan University of Medical Science - Parvaneh Nasri; Vahid Ashourioun; Maryam Avizhgan; Hamid Afshar (مجله ایرانی آموزش در علوم پزشکی, 2012)
Introduction: it is important to identify factors, which lead to academic achievement and impede academic failure. Some psychological elements including positive and negative perfectionism, anxiety and self-esteem seem to be related to academic achievement. This study aimed to measure relationship between psychological profile and academic achievement of medical and dental students at Isfahan University of medical science. Methods: This research was a descriptive-analytic study. Subjects were all medical and dental students who were volunteered to participate in basic sciences comprehensive exam. PANPS scale, SAS scale and Rosenberg self-esteem scale were used for collection data. Their relations with academic achievement (average score and basic science comprehensive exam score) were studied. Result: Comparing means of negative perfectionism showed that there was significant difference between the second group of medical students and dental students (p=0.01). There were significant negative correlations between negative perfectionism with average score (r=-0/44 p=0/01) and comprehensive exam score(r= -0/40 p=0/02 in dental students). There were significant positive correlations between self-esteem and average score (r=0/37 p=0/03) and comprehensive exam score (r=0/45 p=0/00). Conclusion: The Relationship between psychological profile with academic achievement in medical and dental students is difference. It seems that students' academic achievement is also influenced by other factors.